METODE CANVASSING SEBAGAI UPAYA UNTUK MENINGKATKAN PENJUALAN SEPEDA MOTOR HONDA DI PT TUNAS HONDA MERLUNG KECAMATAN TUNGKAL ULU - Surniati; Mustika; Suryani, Ade Irma (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Faced with increasingly fierce business competition, companies are required to continuously develop adaptive and effective marketing strategies. PT Tunas Honda, as one of Honda's official motorcycle dealers, has set a sales target of 200 units per month. However, sales figures for the last four months have fallen short of this target, necessitating an evaluation of the marketing strategy used. This study aims to examine the application of the canvassing method as an alternative direct marketing strategy that is believed to reach consumers in a more personal and targeted manner. The research approach used is descriptive quantitative with data collection through questionnaires, interviews, and documentation. The results of the study show that the canvassing method has contributed positively to increased sales, especially in the months after this strategy was implemented. This finding is reinforced by data showing a significant increase in sales volume in June. Thus, the canvassing method can be an effective strategy for maintaining sales stability outside of peak season, as long as it is supported by competent canvassers, proper regional planning, and attractive promotional programs.